A Toxoplasma gondii thioredoxin with cell adhesion and antioxidant function - Wang, Dawei; Shi, Yuyi; Cheng, Ziwen; Luo, Like; Cheng, Kuo; Gan, Shengqi; Liu, Che; Chen, Zeliang (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundToxoplasma gondii (T. gondii) is a widespread, zoonotic protozoan intracellular parasite with a complex life cycle, which can cause toxoplasmosis, a potentially serious disease. During the invasion process, T. gondii proteins first bind to the relevant host cell receptors, such as glycosaminoglycan molecule (GAG-binding motif), which is one of the main receptors for parasites or virus to infect host cells. However, research on TGME49_216510 (T. gondii Trx21), a protein from Toxoplasma gondii, is limited.MethodsBioinformatics analysis of the Trx21 protein was performed firstly. And specific primers were then designed using the conserved domain and GAG-binding motif to amplify, express, and purify a fragment of the Trx21 protein. The purified Trx21-GST protein was used for antioxidant and cell adhesion experiments. Simultaneously, mice were immunized with Trx21-His to generate specific polyclonal antibodies for subcellular localization analysis.ResultsThe Trx21 protein, consisting of 774 amino acids, included a transmembrane region, three GAG-binding motifs, and a Thioredoxin-like domain. The recombinant Trx21-His protein had a molecular mass of about 31 kDa, while the Trx21-GST protein had a molecular mass of about 55 kDa, which was analyzed by SDS-PAGE and Western blot. Subcellular localization analysis by IFA revealed that Trx21 is predominantly distributed in the cytoplasm of T. gondii. Furthermore, Trx21 exhibited a protective effect on supercoiled DNA against metal-catalyzed oxidation (MCO) and demonstrated adhesion abilities to Vero cells.ConclusionsThese results indicate that Trx21 plays an important role in host cell interaction and oxidative damage.